Heat source estimation in anisotropic materials. (February 2016) - Valès, B.; Munoz, V.; Welemane, H.; Pastor, M.-L.; Trajin, B.; Perrin, M.; Cantarel, A.; Karama, M.
Abstract: The present paper is devoted to the determination of heat source dissipation from infrared thermographic measurements. Such procedure is mainly based on the heat diffusion equation provided by thermodynamics principles. Especially, this requires time and spatial derivation of temperature fields and the knowledge of the material thermal conductivity. This work intends to extend such classical procedure for isotropic materials to the anisotropic context. At first, we propose a comparative study of several filtering methods required for the data processing of noisy and discrete thermal acquisitions. In a second part, a transversely isotropic effective thermal conductivity tensor is estimated by means of a homogenization-based method. From these both results, a heat source application is presented in order to analyze damage phenomena in transversely isotropic CFRP submitted to tensile tests.